APPRECIATION OF CONTEMPORARY CHINESE OIL PAINTING THROUGH CULTURAL CONTEXT - Li Hanchen; Rushana Sulaiman @ Abd Rahim (Journal of Islamic, Social, Economics and Development, 2024)
This paper is for the appreciation of Chinese contemporary oil paintings in Henan Province, and the researcher has chosen the work "Seven Discarded Objects in the Bamboo Forest" by the artist Wang Hongwei of Henan Province, China, as the object of discussion. This work is analysed in terms of formalism, but it is also analysed with the concepts of culture, which exist through values, behaviours, needs, and environments in the field of art. The aim of the research is to identify the subjects and analyse the art forms in the work "Seven Discarded Objects in the Bamboo Forest", and to explain the connection between formalism in the art of painting through the socio-cultural system. The written and visual data collection methodology in this study uses a descriptive qualitative approach based on empirical field work of the data obtained. Documentation, visual records and observation methods were used to gather information related to the paintings under study. The results of the study show that Wang Hongwei's work "Seven Discarded Objects in the Bamboo Forest" was created by applying traditional Chinese cultural elements and philosophical concepts to the art of oil painting and utilising the principles of artistic design. The significance of the study shows that contemporary Chinese oil paintings in Henan Province cannot be viewed only from the formalistic perspective of art, but also shown through the cultural context. This study contributes to understanding the meanings, concepts and purposes of design employed by contemporary Chinese artists in shaping the image of their paintings.